Aspectos da dinâmica populacional e reprodutiva de Pimelodus maculatus (Siluriformes, Pimelodidae) no reservatório de Cachoeira Dourada (GO-MG) - Sabinson, Lia Mayrink (2009)
Growth and reproduction parameters of the yellow-mandi, Pimelodus maculatus (LACÉPÈDE, 1803) (Siluriformes, Pimelodidae), were determined for the Cachoeira Dourada reservoir (GO-MG). The field work occurred throughout February 2007 to January 2008 (with the exception of December 2007). Gill nets with mesh sizes from 1, 5 to 10 centimeters were placed in three different areas in the reservoir and were collected 24 hours later. A total of 538 specimens were captured, amongst which 242 were females, 219 males and 77 could not have their gender determined. Sex ratio differed from 1:1 only during July 2007 and January 2008, with males and females predominating in each of those months. Males occupied the medium length classes (18,9 to 24,3 cm) while females were most abundant in the superior classes (from 27 to 37,8 cm).The L50 for males were 24,8 cm and 26,2 cm for females. The growth constant K assumed a higher value for females (K=0,1356) than for males (K=0,0383), revealing a much faster growth rate for the females of P. maculates, which may be due to their greater investment in reproductive tissue, a fact also indicated by the elevated values of Kn and GSI during the summer. Having in mind that P. maculatus reproduces in the rainy season, a greater gain in weight is expected during the months before the reproduction season, and that after it occurs the fish loses fat and weight as a consequence of metabolic effort. The reduction in the ecosystems complexity is consequence of the reduction in the surrounding diversity, and it seems to be the main factor modifying the population`s and reproductive dynamics of Pimelodus maculatus in the Cachoeira Dourada reservoir.